2017
DOI: 10.6061/clinics/2017(04)06
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and associated factors: a cross-sectional study of bank employees

Abstract: OBJECTIVE:Insulin resistance is characterized by the failure of target cells to respond to normal levels of circulating insulin, and this condition is related to cardiovascular disease. This study sought to evaluate the prevalence of insulin resistance and its association with markers of metabolic abnormalities and metabolic syndrome in bank employees.METHODS:A cross-sectional study was performed on 498 working men and women aged ≥20 years old. The Homeostasis Model Assessment (HOMA-IR) was used to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
2
7
0
2
Order By: Relevance
“…This was a cross-sectional observational study, with data derived from a study on MetS, insulin resistance, and associated factors in bank employees. 8 , 10 The sample analyzed consisted of full-time employees of a banking network, August 2008 to August 2009, in Greater Vitória, ES, Brazil, aged between 20 and 64 years, for both genders.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a cross-sectional observational study, with data derived from a study on MetS, insulin resistance, and associated factors in bank employees. 8 , 10 The sample analyzed consisted of full-time employees of a banking network, August 2008 to August 2009, in Greater Vitória, ES, Brazil, aged between 20 and 64 years, for both genders.…”
Section: Methodsmentioning
confidence: 99%
“…Data on metabolic syndrome and sociodemographic and labor factors have already been published. 8 , 10 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The scientific literature still lacks studies determining the prevalence of IR in the Brazilian population, but a study evaluating IR in a representative sample of Brazilian workers found a prevalence of 10.4% (5). In rural populations, this is even more scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Os presentes resultados mostram que os participantes do ELSA-Brasil com maior consumo de carne total também apresentaram maior adiposidade abdominal, menor tempo semanal de atividade física e maior consumo de álcool. Há evidências de que esses fatores influenciam a ocorrência RI e DM (27-30). Desse modo, essas variáveis foram consideradas no modelo ajustado, bem como outras que também estiveram relacionadas com o desfecho e a exposição.…”
Section: Discussionunclassified